Utilizing the Demonstration Method to Enhance Science Learning Outcomes: A Classroom Action Research at SDN Kebagusan 02 Pagi, South Jakarta - Hermawan, Cecep Maman; Hesti; Anjani, Lalita Shafa; Fuadah, Syifa Fitri Fuadah; Gani, Irfan Abdul; Rosfiani, Okta (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
This classroom research is motivated by the learning outcomes of third grade students at SDN Kebagusan 02 which still need to be improved. The purpose of this study was to improve student learning outcomes in science subjects on the material of changes in the properties of objects at SDN Kebagusan 02 Pagi. This research method, using a class action method with a cycle system while the learning model is a demonstration method where the teacher demonstrates or shows something in front of students, which is done inside or outside the classroom. The results of this study are that the pre-cycle or completeness meets the KKM 24.42%, in cycle I completeness 64.28% meets the KKM, and in cycle II it meets the KKM 100%. Based on the results of observations, it can be concluded that the demonstration method learning model of science subjects’ changes in objects in class III. As for other data related to research and student work results as in the appendix. Finally, the researcher suggests to all teachers to be creative in presenting learning, especially in using props and media that are interesting and varied so that they can bring students in a pleasant learning process and complete student learning outcomes can be achieved.